Sociodemographic factors associated with knowledge and adequate attitudes about HIV in women of reproductive age from Peru - Isaac Echenique; Willer Chanduvi; Willy Ramos; Marcos Saavedra-Velasco; Jhony A. De La Cruz-Vargas; Ericson L. Gutierrez (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: To determine the sociodemographic factors associated with knowledge and adequate attitudes about HIV in women of reproductive age from Peru in 2021. MATERIALS AND METHODS: Analytical cross-sectional study. We analyzed a demographic and family health survey (ENDES) 2021 carried out in women of reproductive age (12 to 49 years of age). The dependent variables were the adequate level of knowledge and adequate attitudes about HIV, the independents were sociodemographic variables. The statistical analysis was carried out with a Poisson regression model with robust variance obtaining the adjusted prevalence ratio (PRa) and confidence intervals. RESULTS: Thirty-four percent (CI 95%: 32,9-35,1) had an adequate level of knowledge about HIV and 32,9% (CI 95%: 31,7-34,0) had adequate attitudes. In the multivariate analysis, the main variables associated with the adequate level of knowledge about HIV were the higher level of education (PRa = 1,19; CI 95%: 1,15-1,23) and very rich wealth quintile (PRa = 1,15; CI 95%: 1,01-1,20); while the main variables associated with adequate attitudes on HIV were higher level of education (PRa = 1,44; CI 95%: 1,40-1,48), high-school education level (PRa = 1,21; CI 95%; 1,18-1,24), very rich wealth quintile (PRa = 1,18; CI 95%: 1,14-1,22), and age range between 35 and 49 years (PRa = 1,18; CI 95%: 1,15-1,21). CONCLUSIONS: The sociodemographic factors associated with knowledge and adequate attitudes about HIV in Peruvian women of reproductive age were mainly higher level of wealth, higher level of education, and a higher age range. Other sociodemographic variables presented a weak association with knowledge and adequate attitudes about HIV.